Case report: Extrapontine myelinolysis combined with flupentixol- and melitracen-induced dysphagia - Zhao, Zhihong; Han, Lu; Zhu, Zilong (Frontiers in Pharmacology, 2023)
Extrapontine myelinolysis (EPM) is a rare symmetrical demyelinating disease of the central nervous system, which is often accompanied with central pontine myelinolysis (CPM) or can appear alone. A combination of flupentixol and melitracen is used as an antianxiety–antidepressant drug which may induce hyponatremia. Herein, we report a 46-year-old woman with depression who was treated with flupentixol and melitracen 0.5/10 mg once daily for 6 months. Later, the dosage increased to 0.5/10 mg twice daily. At the same time, she had complains of intermittent dizziness and fatigue. The laboratory test revealed hyponatremia (121 mmol/L). Dizziness was improved after sodium supplementation, with an increase in blood sodium to 133 mmol/L. Twenty days later, she had difficulty opening the mouth and swallowing, needing a gastric tube due to severe dysphagia. Head magnetic resonance imaging (MRI) showed a symmetric abnormal signal of caudate nucleus and lenticular nuclei. The symptoms were not relieved after active treatment, such as rehydration. However, her symptoms improved significantly after discontinuation of flupentixol and melitracen and switching to promethazine. Follow-up head MRI after 4 months revealed no abnormal signals. The patient who developed EPM had dysphagia, despite appropriate correction of hyponatremia. Flupentixol and melitracen can cause hyponatremia and dysphagia. This case highlights an unexpected association between EPM and flupentixol- and melitracen-induced dysphagia.